Steel-reinforced concrete structures : assessment and repair of Corrosion - El-Reedy, Mohamed A. (CRC Press, 2008)
A Practical Guide to Maintenance Carrying a billion-dollar price tag, corrosion of reinforced concrete is the enemy of every country's investment in real estate. The widespread and long-term use of reinforced concrete makes its correct and proper examination, maintenance, and repair paramount. Steel-Reinforced Concrete Structures: Assessment and Repair of Corrosion explains the corrosion of reinforced concrete from a practical point of view, highlighting protective design and repair procedures. The book begins with a discussion of the corrosion phenomena, the.